Sibling Inequalities in Overweight and the Role of Mother's Education: Evidence From the Indonesian Family Life Survey. Issue 1 (June 2021) - Kunto, Yohanes Sondang; Bras, Hilde
Background: Previous studies have shown that sibling inequalities in overweight vary across contexts. Furthermore, research on the extent to which parental factors such as mother's education can compensate for or reinforce such disparities is considerably rare. Objective: This study analyzes to what extent and how the chances of overweight among children (0-19 years of age) vary systematically by gender, birth order, and number of siblings. We also look at whether mother's education buffers or aggravates sibling inequalities in overweight. Methods: Data were from the fifth wave of the Indonesian Family Life Survey-5 2014/2015, which comprised 6723 children born in 4784 families. We applied within-family centered birth order dummies to disentangle the effects of birth order from those of number of siblings. Cluster-robust logistic regressions were conducted. Results: Overweight occurred more in eldest and youngest children, and in children of smaller families. Mother's education amplified sibling inequalities. Odds of overweight in children increased along with more years of education the mothers had. This was greater for boys and eldest children. Further analyses indicated that boys whose mothers spent more years in school consumed high-calorie foods more often. Conclusion: The overall results indicate that mother's education aggravates sibling inequalities in overweight. Nutrition interventions to reduce overweight in children should target the eldest and the youngest children and children of smaller families. Mothers who had more school years, and particularly their sons, should also be in the target group. Boys should be advised to consume high-calorie foods less often.